The impact of sharia compliance on the adjustment to target debt maturity of Malaysian firms - Hussain H.I.; Shamsudin M.F.; Anwar N.A.M.; Salem M.A.; Jabarullah N.H. (International Strategic Management Association, 2024)
Indexed by SCOPUS